Evaluation on microalgae for the production of bio-chemicals and electricity - Khairuddin, Farahayu; Mohd Fuzi, Siti Fatimah Zaharah; Ahmad, Awais; Low Kheng Oon, Low Kheng Oon; Bokhari, A.; Daniel Joe Dailin, Daniel Joe Dailin; A. Habila, Mohamed; Alam Nawaz, Alam Nawaz; L.F. Chuah, L.F. Chuah (Elsevier, 2024)
Recent advancement in biophotovoltaic systems using microalgae, coupled with biorefinery approach, would improve economy-feasibility in production. The major concern is its commercial strength in terms of scalability, strain selection and extraction procedure cost. It must compete with conventional feedstocks such as fossil fuels. This project proposes to enhance the economic feasibility of microalgae-based biorefinery by evaluating their performance for bio-electricity, bio-diesel and carotenoids production in a single cycle. The first part of the study was to construct and select a Bio-bottle Voltaic (BBV) device that would allow microalgae to grow and produce bioproducts, as well as generate the maximum current output reading derived from the microalgae’s photosynthesis process. The second phase consisted of a 25-day investigation into the biorefinery performance of six different microalgal species in producing bio-electricity, bio-diesel and carotenoid in a prototype BBV device. The prototype BBV device with aluminium foil and pencil lead as its anode and cathode produced the highest carotenoid and biodiesel component production from the two microalgae tested, according to the results of the first phase of the experiment. In the second portion of the study, Scenedesmus dimorphus and Chlorella vulgaris were identified as the two microalgae most capable of maintaining their growth throughout the experiment. The maximum current reading observed for C. vulgaris was 653 mV. High Performance Liquid Chromatography analysis showed four major carotenoid compounds found which were Neoxanthin, Cantaxanthin, Astaxanthin and 9-cis antheraxanthin, and the highest carotenoid producer was C. vulgaris which recorded at 1.73 μg/mL. C. vulgaris recorded as the most alkanes producer with 22 compounds detected and Heptacosane and Heneicosane as the two major biodiesel compounds found in the extracts. Evaluation of C. vulgaris data showed that it has enormous potential for microalgal biorefinery candidates. Further ongoing research and development efforts for C. vulgaris will improve the economic viability of microalgae-based industries and reduce reliance on depleted fossil fuels.